MicroRNA biogenesis machinery activation and lncRNA and REST overexpression as neuroprotective responses to fight inflammation in the hippocampus - Carvalho, Liebert Bernardes (2023)
Brain Long non-coding RNA (lncRNA) and microRNAs (miRs) play essential roles in the regulation of several important biological processes, including neuronal activity, cognitive processes, neurogenesis, angiogenesis, and neuroinflammation. In this context, the transcriptional repressor, RE1 silencing transcription factor (Rest), acts regulating the expression of neuronal genes as well as of lncRNAs and multiple miRNAs in the central nervous system. Nevertheless, its role in neuroinflammation was less explored. Here, we demonstrate, using an in vivo model of neuroinflammation induced by i.p. injection of LPS (0.33 mg/kg), that neuroinflammation increases gene expression of pro-inflammatory cytokines concomitant with the native and truncated forms of Rest and of non-coding RNAs. Additionally, the increased expression of enzymes Drosha ribonuclease III) (Drosha), Exportin 5 (Xpo5) and Endoribonuclease dicer (Dicer), associated with high expression of neuroprotective miRs 22 and 132 are indicative that the activation of biogenesis of miRs in the hippocampal region is a Central Nervous System (CNS) protective mechanism for the deleterious effects of neuroinflammation. Our results indicate that positive regulation of Rest gene expression in the hippocampal region by neuroinflammation correlates directly with the expression of miRs 22 and 132 and inversely with miR 335. In parallel, the confirmation of the possible alignment between the lncRNAs with miR 335 by bioinformatics corroborates with the sponge effect of Hottip and Hotair hybridizing and inhibiting the pro-inflammatory action of miR 335. This suggests the existence of a possible correlation between the activation of miR biogenesis machinery with increased expression of the transcription factor Rest, contributing to neuroprotection.